Akuntabilitas Pengelolaan Keuangan Desa Berdasarkan Filosofi Tri Hita Karana di Desa Buduk, Kecamatan Mengwi, Kabupaten Badung - Reksa Armajaya, I DG. Taksusepta; Purnamaningsih, Putu Eka; Supriliyani, Ni Wayan (CITIZEN CHARTER; Vol 1 No 01 (2021): Administrasi Publik 2021, 2022)
The realization of accountability can also be supported from several factors, the factors that can support it is the culture of an area. Tri Hita Karana is a Hindu religious philosophy that is always present in every aspect of the life of indigenous peoples in Bali. This study aims to describe the accountability of village financial management based on Tri Hita Karana philosophy in Buduk Village. The research approach used is descriptive qualitative research and data collection methods in the form of observation, interviews, and documentation. This study measures how accountability in village financial management based on the Tri Hita Karana philosophy in Buduk Village using the theory of financial accountability which has 3 (three) indicators, transparency, accountability, and the principle of value of money. The results of this study show that the Buduk Village Government has implemented village financial management in accordance with the Tri Hita Karana concept well.